Saúde de mães e crianças de uma comunidade antes e após o seu reconhecimento como quilombola - Torres, Zaira Maria Camerino (2013)
Quilombos Brazilians and the remaining areas are the result of a historical process of the formation of the Brazilian nation, which originated in the Portuguese colonization. The formation of the Quilombo occurred as a form of resistance to the regime of slavery during the colonial Brazil and even in the Empire, and to the present day are occupied by people without full recognition of society. The living conditions of this ethnic group have not been the most favorable, and it is known that social and material conditions indirectly influence the health / disease process, and consequently, the life expectancy of these minorities. The process of health / illness is the result of a historical process that involves the issue of social inequalities. For this reason, it is important to prioritize the search for equity through access to health care and utilization of services that promote improvement in the quality of care of these specific populations. This study aimed to investigate the health situation in a community (Bom Despacho) before and after its official recognition as “quilombola”. To this end, we present a literature review chapter, covering the history, training and health of maroon communities. In addition to an original article which aimed to describe this study aimed to investigate the health situation in a community (Bom Despacho) before and after its official recognition as “quilombola”. This is a transversal study involving the set of children and women in the community Good Order, Step Camaragibe. Through visits to all households in the community were obtained demographic, socioeconomic and health. The survey was conducted in 2012. We used data from a similar survey conducted in 2008 to allow analysis of the evolution of the indicators. The data come from of two independent cross-sectional studies (2008, 2012), in which were eligible women and children of all households (143 in 2008, 171 in 2012). To analyze the time trend, we used the prevalence ratio. In 2012, 62.8% of women had BMI>25kg/m2, 57.4% waist circumference ≥ 80cm and 33.9% hypertension. Among the children, 10.9% had statural deficit, 9.4% overweight, 20.0% anemia and 26.9% diarrhea. The indicators that presented significant (p <0.05) evolution (2008; 2012) were: average income per capita (R$ 96.66; R$ 189.05), diarrhea in children (10.3%; 26.9%), vitamin A supplementation (70.2%; 100.0%), exclusive breastfeeding ≥ 6 months (8.7%; 44.7%); children’s immunizations calendar updated (95.3%; 80.3 %) and anemia in children (40.2%; 20.0%). There were improvements in several indicators, however, the observed situation still requires investments aiming to increase the standard of health in the studied community. Public policies are needed to combat social inclusion prejudice and inequalities affecting the fraction of the population, with shares ranging from infrastructure issues basic to quality education, health, access to information and rights and duties.